Fugitive film copyright: research on the influencing factors of users watching pirated film and television works - Wang Jingwen; Yang Yisong (Social Influence)
The global dissemination of piracy film and television content has given rise to significant concerns in the advent of the Internet and digital media. This study employs neutralization theory as a mediating variable to examine the relationship between perceived benefits and harms of pirated content, and piracy behaviour. The empirical analysis is based on 503 valid online questionnaires, and structural equation modeling was conducted with IBM SPSS 26.0 and AMOS 23.0. The results obtained demonstrate that users’ perceptions of the benefits of piracy, their perceived harm to artists and producers, and their rationalisation of past piracy are linked to piracy behaviour. These findings provide insights into the motivations behind piracy, contributing to a better understanding of the issue.